Assessment of pain management intervention for treatment of long bone fractures in tertiary care hospital - Sada, Elizabeth C.; Bhot, Firdaus; Kanishetty, Rohit (International Journal of Advances in Medicine, 2019)
Background: Musculoskeletal trauma represents a considerable global health burden. Pain is a complex, subjective personal experience. The assessment of pain is the essential perquisite for successful pain management. It is useful to decide the plan of initial treatment but also to reassess the degree of success. So the purpose of the study was to do assessment of pain management intervention, post-op analgesics for treatment of long bone fractures. Methods: All adult patients (more than IS years) reporting to Emergency Medicine Department of a tertiary care hospital with long hone fractures of lower limb were included in the study. Patient pain management was assessed by visual analogue score (VAS). Pain is a complex, subjective personal experience. The assessment of pain is the essential perquisite for successful pain management. It is useful to decide the plan of initial treatment but also to reassess the degree of success. The entire data is statistically analyzed using SPSS software. p-values less than 0.05 are considered to be statistically significant. Results: 74 cases got operated, 64 cases (86.5.0%) did not have any intra-op complications and 10 cases (13.50%) had intra-op complications .Postoperative analgesia the 74 cases operated was as follows: 17 cases (23.0%) epidural anaesthesia 41 Cases (55.4%) had epidural + intravenous analgesics. Recent was managed with 1.V, analgesics alone; 12 cases (16.20%) had tramadol, 2 cases (2.7%) received paracetamol and 2 cases (2.7%) had dynaper for post-operative analgesia. Conclusion: Adequate pain management on arrival in the Emergency Department is an important aspect in patient care and is not at all difficult to achieve. Femoral nerve block in Proximal lower limb fractures is very effective and easy to perform.